(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
Traditional lecture-based approach with laboratory-based exercises is commonly used to teach cybersecurity. It is useful to provide hands-on experience to students. However, it fails to provide students an opportunity to completely explore the multi-faceted and ill-defined problems prevalent in the real-world cybersecurity scenarios. Problem-based learning is a student-centered pedagogy in which students are presented with complex, open-ended, real-world problems to promote learning of concepts and principles, contrary to the traditional lecture-style presentations. Over the years, the model has been adopted to teach concepts in other disciplines including economics, business administration, architecture, law, engineering and social work, however, there has been little work done in the field of cybersecurity. This paper illustrates the use of problem-based learning for cybersecurity education along-with an open cyber range architecture for preliminary implementation. This student-focused and active learning pedagogy has proven to not only provide students with an opportunity to learn relevant concepts, tools and techniques applicable to the given problem but also improve focus, interest, motivation, and foster lifelong learning skills, essential to survive in ever-changing cybersecurity field.